(untitled) (E Global Congress, 2026)
This article analyzes the level of scientific study of ethnocultural tourism based on the research of foreign, CIS, and Uzbek scholars. It also examines methodological approaches used in studying ethnocultural tourism through the case of Bakhmal and Gallaaral regions. As a result of the study, the opportunities for the development of ethnocultural tourism in these regions and scientific research methods are identified.